Between Two Fires? Austro-Hungarian Soldiers of Italian Origin during World War I. Review of: Di Michele, A. (2022). Mezh dvukh mundirov. Italoiazychnye poddannye Avstro-Vengerskoi imperii na Pervoi mirovoi voine i v russkom plenu [Between Two Uniforms. Italian-Speaking Subjects of the Austro-Hungarian Empire in World War I and in Russian Captivity] (M. G. Talalay, Trans. & Ed.). Italiia — Rossia. St Petersburg: Aleteja, 2022. 286 p., ill - Surzhikova, Natalia V. (Izvestiâ Uralʹskogo federalʹnogo universiteta. Seriâ 2, Gumanitarnye nauki, 2022)
This review considers the study by A. Di Michele, professor at the Free University of Bolzano (South Tyrol), dedicated to the pre-war and military experience, as well as the experience of captivity of Italian-speaking soldiers of the Austro-Hungarian army during World War I. The main emphasis is placed on its role in the process of their ethno-cultural and ethno-political self-identification, directly related to the population and identity politics pursued by the states of Europe and Russia in the second half of the nineteenth — first quarter of the twentieth centuries. It demonstrates what gaps A. Di Michele’s study is able to fill and what problems to actualise, focusing simultaneously on the regional, national, and supranational contexts of the topic of Austro-Hungarian soldiers of Italian origin during World War I and in Russian captivity.